Preliminary genome assembly of the Wolbachia endosymbiont of the South American fruit fly, Anastrepha fraterculus sp. 1. - Conte, Claudia Alejandra; Rivarola, Maximo Lisandro; Gonzalez, Sergio Alberto; Russo, Romina Maria; Scannapieco, Alejandra Carla; Wulff, Juan Pedro; Handler, Alfred M.; Ragoussis, Ioannis; Segura, Diego Fernando; Bourtzis, Kostas; Lanzavecchia, Silvia Beatriz (MDPI, 2025)
Poster